The Effect Of Circuit Training on Improving The Resistance Of The Muscle Strength Of The Pertina Club - Sugiarto, Sugiarto; Carnegi, Dale; Dinata, Benny Fika (Jurnal Guru Peneliti Professional, 2019)
The problem in this study is the lack of endurance in the arm muscle strength of the boxing athletes in the Pertina club, Padang City. This study aims to see how circuit training increases the endurance of the arm muscle strength of the boxing athletes in the Padang City Club Pertina. This type of research is an experiment, which was conducted in the Gor H. Agus Salim sports hall / field, starting from October 2017 to November 2017. The population of this study was the boxing athletes of the Pertina club in Padang City, totaling 30 people consisting of 22 men. and 8 women and then taken a sample of 20 people, and divided into 14 men and 6 women to be studied. After that, the treatment was given 16 times. The data collection technique used the Push Up test. The collected data is used to test the hypothesis using the t-test. From the results of this study it can be concluded as follows that there is an effect of the circuit training method on increasing the endurance of the arm muscle strength of the boxing athletes of the Padang City Pertina Club with (4.21)> (1.73) at ???? = 0.05, where the average strength endurance ability arm muscles on the initial test 23.15 while the final test increased to 27.95. This means that there is an increase in the endurance capacity of the arm muscles using the circuit training method.